Innovative Strategies in Managing Early-Onset Primary Congenital Glaucoma - Imelda, Eva; Ghassani, Vania (Indonesian Journal of Case Reports, 2024)
Congenital glaucoma has the potential to damage the visual nerve fibers, leading to permanent blindness. This case report aims to provide timely and appropriate management upon diagnosis. The case involves a 5-month-old baby girl delivered via spontaneous normal delivery at 36-37 weeks, with a birth weight of 3100 grams, who presented with complaints of left eye enlargement since one month of age, persistent watery eyes, and photophobia when exposed to sunlight. Diagnoses included Primary Congenital Glaucoma, Congenital Cataract, and Exotropia Oculi Sinistra. The patient received preoperative medication, underwent trabeculotomy-trabeculectomy surgery, and had CRS screening and Rubella serological examination. Early detection and operative intervention to regulate intraocular pressure can preserve optimal visual function throughout adulthood.